Design and Optimization of the VideoWeb Wireless Camera Network. (18th August 2010) - Nguyen, Hoang Thanh; Bhanu, Bir; Patel, Ankit; Diaz, Ramiro
Abstract : Sensor networks have been a very active area of research in recent years. However, most of the sensors used in the development of these networks have been local and nonimaging sensors such as acoustics, seismic, vibration, temperature, humidity. The emerging development of video sensor networks poses its own set of unique challenges, including high-bandwidth and low latency requirements for real-time processing and control. This paper presents a systematic approach by detailing the design, implementation, and evaluation of a large-scale wireless camera network, suitable for a variety of practical real-time applications. We take into consideration issues related to hardware, software, control, architecture, network connectivity, performance evaluation, and data-processing strategies for the network. We also perform multiobjective optimization on settings such as video resolution and compression quality to provide insight into the performance trade-offs when configuring such a network and present lessons learned in the building and daily usage of the network.